Utilization of Powdered Eggshell Waste for Rhodamine B Removal: Evaluation of Adsorptive Efficiencies and Modeling Studies - Wahiba Bessashia; Zhour Hattab; Yamina Berredjem; Ridha Djellabi; Radia Zerdoum; Assia Allaoui; Abdelhak Gheid; Kamel Guerfi (American Scientific Publishers, 2018)
Biomass wastes are being recognized as emerging functional platforms that can be utilized in various fields. Eggshell, which can be found everywhere due to the large eggs consumption, has usually been regarded as waste and overlooked. In this contribution, we report the use of three powders prepared from eggshell waste such as Eggshell without membrane (ES), Eggshell membrane (ESM) and Eggshell with membrane (ESM-ES) as biosorbents for the removal of Rhodamine B (RhB) from water. Biosorbent powders were characterized by XRD, SEM, BET and FTIR. The effects of initial RhB concentration, temperature and pH on dye adsorption were performed. The results showed that the ESM, due to its 3D network porous structure, exhibited the highest adsorption efficiency than ES and ES-ESM. The RhB sorption on these adsorbents obeys pseudo-second-order kinetics which indicates a chemisorption process. For ESM adsorbent, the Freundlich isotherm model has a best-fit compared to Langmuir and Temkin isotherm models (multilayer dye adsorption with non-uniform distribution). However, for ES and ESM-ES adsorbents Langmuir has a best-fit than the other models (monolayer dye adsorption).